The Content of Scientific Explanations Aspect in The Junior High School Science Textbooks: An Analysis on Substance Pressure Topics - Fatikhiah, Fina Al; Siswanto, Siswanto; Dewantari, Nuryunita; Singgih, Suwito; Amirul, M. Ardi (Journal of Natural Science and Integration, 2022)
The purpose of this research is to compare the aspects of scientific explanation and identify the patterns of scientific explanation in several books. The textbooks sampled in this study were (Sample 1) Science Textbooks for junior high school grade 8th Curriculum 2013 Revised Edition 2017 published by the Ministry of Education and Culture of the Republic of Indonesia, (Sample 2) Integrated Science Books for junior high school grade 8th Curriculum 2013 published by Yudhistira, (Sample 3) Science Books for junior high school grade 8th Curriculum 2013 published by Gramedia. This research uses a qualitative descriptive approach with content analysis. The data collection technique used a document content review technique in the sample book. The validity of the data used is a confidence test, a transferability test, a dependency test, and a certainty test. For data analysis using fixed comparison method which includes data reduction, organization, categorization, synthesis, and formulating working hypotheses. From this study, it was found that the scientific explanation can only be identified if it fulfills the three main components described, namely claim, evidence, and reasoning. The three book samples have uniformity in the content of scientific explanation aspects. The three all have categories of claim only (C), claim-evidence (C-E), and claim-evidence-reasoning (C-E-R). However, the sample 1 has the greatest level of density. Its mean that the sample 1 presents the most complete scientific explanation aspects when compared to the presentation of the claim aspects. The research show that in preparing junior high school science textbooks, it is necessary to pay careful attention to the completeness of the scientific explanation aspect. This is because it is very important to facilitate this for students.Keywords: Scientific Explanation, Science Textbooks, Substance Pressure.